Characteristics of metabolic stability and the cell permeability of 2‐pyrimidinyl‐piperazinyl‐alkyl derivatives of 1H‐imidazo[2, 1‐f]purine‐2, 4(3H, 8H)‐dione with antidepressant‐ and anxiolytic‐like activities. (4th December 2018) - Zagórska, Agnieszka; Partyka, Anna; Bucki, Adam; Kołaczkowski, Marcin; Jastrzębska‐Więsek, Magdalena; Czopek, Anna; Siwek, Agata; Głuch‐Lutwin, Monika; Bednarski, Marek; Bajda, Marek; Jończyk, Jakub; Piska, Kamil; et al.
Abstract: A series of 2‐pyrimidinyl‐piperazinyl‐alkyl derivatives of 1H‐imidazo[2, 1 ‐f ]purine‐2, 4(3 H, 8 H )‐dione has been synthesized in an attempt to discover a new class of psychotropic agents. Compounds were evaluated for their in vitro affinity for serotonin 5‐HT1A, 5‐HT7, and phosphodiesterases PDE4 and PDE10. The most potent compound 2‐pyrimidinyl‐1‐piperazinyl‐butyl‐imidazo[2, 1 ‐f ]purine‐2, 4‐dione (4b ) behaved as strong and selective antagonist of 5‐HT1A . Molecular modeling studies revealed differences in binding mode between compound4b and buspirone, which might reflect variation of the ligands' affinity and potency in the 5‐HT1A receptor. Compound4b in silico models demonstrated drug‐likeness properties and, contrary to buspirone, showed a metabolic stability in mouse liver microsomes system. Experimentally obtained value of apparent permeability coefficient P app for4b in parallel artificial permeability assay indicates the possibility of binding weakly to plasma proteins and high intestinal absorption fraction. Evaluation of the antidepressant‐ and anxiolytic‐like activities of4b revealed both activities at the same dose of 1.25 mg/kg and seemed to be specific. The antidepressant and/or anxiolytic properties of4b may be related to its first‐pass effect. Abstract : From the series of 2‐pyrimidinyl‐piperazinyl‐alkyl derivatives of 1H‐imidazo[2, 1 ‐f ]purine‐2, 4(3 H, 8 H )‐dione, compound4b behaved as antagonist of 5‐HT1A with antidepressant‐ and anxiolytic‐like activity. The antidepressant and/or anxiolytic properties of4b may be related to its first‐pass effect.